MÉNINGITE BACTÉRIENNE AIGUE COMMUNAUTAIRE CHEZ L’ADULTE ET L’ENFANT À L’HÔPITAL MIXTE COLONEL LOTFI ET L’HÔPITAL HMIDA BENADJILA À LAGHOUAT (2018 -2023). - BRAHIMI Ahlem; BENSADOK Kaltoum; LABIAD Marwa Inas (université ammar telidji laghouat, 2023)
Bacterial meningitis is a major diagnostic and therapeutic emergency. The etiologies are numerous and vary depending on age. In community situations, the most common bacteria remain Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae, followed by Listeria monocytogenes, Escherichia coli, and Staph. Objective : The aim of this work is to conduct a retrospective and descriptive epidemiological study of patients with meningitis. Equipment and methods : A total of 75 patients aged over 28 days are admitted and treated over a period of 6 years (2018 until 2023), with meningitis confirmed by the analysis of the CSF at the level of infectious diseases and pediatric services of the two hospital of ŖAhmad Ben Adjila and the Laghouat El Akide Lotfi Joint Hospital," of the town of Laghouat. Data collection: epidemiological, clinical, and biological parameters and therapeutic attitudes were collected from analyzed medical record. Results and discussion : After analyzing the results, we found that meningitis is common in infants at 42.7%, with a male predominance at 72%. Regarding the vaccination status of our patients against pneumococcus and Hib, we find that 71% of the patients were not properly vaccinated. The clinical signs found were dominated by fever and functional meningitis syndrome and biological infectious syndrome (CRP, leukocytosis). In the macroscopic study of CSF, the disorderly appearance was found in 50% of cases, and a nonnegligible percentage of the clear appearance was found in approximately 33% of patients. The pathogens identified were: S pneumoniae (08/75), N meningitidis (01/75), and H influenzae (01/75). Treatment of bacterial meningitis is of absolute urgency. The prognosis depends on how quickly appropriate antibiotic therapy is initiated, as it can lead to serious complications such as hydrocephalus, epilepsy, andeven death. Keywords : bactériale meningitis, community, epidemiology